24. Equinus foot: A clinical bridge between orthopedy and neurology. Paediatric epidemiology and diagnostic–therapeutic flowchart. Issue 1 (January 2015) - Molesti, E.; Bernocchi, B.; Novembri, A.; Pagliazzi, A.; Marinoni, M.; Bastianelli, M.; Gabbanini, S.; Trapani, S.; Gallerini, A.; Lori, S.
<x xml:space="preserve">Abstract</x> Neuromuscular diseases, in paediatric age, represent a diagnostic and therapeutic challenge: they are progressive, invalidant and often their clinical presentation, like the equines-foot, constitute a bridge between Neurology and Orthopedy. The aims of this study are:1) present epidemiology of clinical cases observed in our Neuro- Orthopaedic outpatient experience from 2009 to 2014; 2) propose a diagnostic and therapeutic flow-chart to a better overview and management of pediatric equines-foot. We clinically evaluated 600 new patients: 480 showed a mono/bi-lateral motor-deficit of lower limbs. Of these 480: 14 were identified as cerebral palsy, 70 needed further neurophysiological (ENG/EMG) and/or neuromuscular- ultrasound-study to set the diagnosis. In 27 on 70 patients, a neuromuscular and/or spinal-cord disease was confirmed with the help of MRI, genetic and immunohistochemistry tests. In remaining 43 cases the negativity of neurophysiological study directed the diagnosis to orthopaedic-sphere with the exception of 4 clinical uncertain cases which required clinical follow-up. Through this diagnostic algorithm each neurological subject was directed to a focused neuro-rehabilitation (physiotherapy, botulinum toxin, supports) and/or to surgery. A Neuro-Orthopaedic diagnostic and therapeutic flow-chart to overview the paediatric equinus-foot facilitates the management of patient establishing area of competence, therapeutic and/or rehabilitative-priority and optimizing human ansi?d scientific resources.